2003
DOI: 10.1051/0004-6361:20031311
|View full text |Cite
|
Sign up to set email alerts
|

The first CCD photometric study of the open cluster NGC 2126

Abstract: Abstract. We present the first CCD photometric observations of the northern open cluster NGC 2126. Data were taken on eight nights in February and December 2002 with a total time span of ∼57 hours. Almost 1000 individual V-band frames were examined to find short-period variable stars. We discovered six new variable stars, of which one is a promising candidate for an eclipsing binary with a pulsating component. Two stars were classified as δ Scuti stars and one as Algol-type eclipsing binary. Two stars are slow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 21 publications
5
17
1
Order By: Relevance
“…Based on the PDM code, we derive a probable period to be 0.0827 d which is close to the f 1 , and the amplitude is 0.104 mag, very low. Combining the results of Gáspár (2003) and of this paper, V5 may be confirmed to be δ Scuti star. V6: Gáspár (2003) showed that V6 was an eclipsing binary system with a δ Sct-type pulsating with P pul = 0.129 d and P orb = 1.1732 d, and it might have f pul : f orb = 1 : 9 resonance between the orbital motion and pulsation.…”
Section: The Known Variables In Ngc 2126supporting
confidence: 73%
See 4 more Smart Citations
“…Based on the PDM code, we derive a probable period to be 0.0827 d which is close to the f 1 , and the amplitude is 0.104 mag, very low. Combining the results of Gáspár (2003) and of this paper, V5 may be confirmed to be δ Scuti star. V6: Gáspár (2003) showed that V6 was an eclipsing binary system with a δ Sct-type pulsating with P pul = 0.129 d and P orb = 1.1732 d, and it might have f pul : f orb = 1 : 9 resonance between the orbital motion and pulsation.…”
Section: The Known Variables In Ngc 2126supporting
confidence: 73%
“…Combining the results of Gáspár (2003) and of this paper, V5 may be confirmed to be δ Scuti star. V6: Gáspár (2003) showed that V6 was an eclipsing binary system with a δ Sct-type pulsating with P pul = 0.129 d and P orb = 1.1732 d, and it might have f pul : f orb = 1 : 9 resonance between the orbital motion and pulsation. Our results of P pul = 0.12957 d and P orb = 1.1732 d are consistent with Gáspár (2003).…”
Section: The Known Variables In Ngc 2126supporting
confidence: 73%
See 3 more Smart Citations